Difficulties of Ibaloy learners of English simple primary conjunctions - Anis, Basilio 1929- (s.n.], 1971)
The difficulties of Ibaloy learners in the use of English simple primary conjuctions were predicted in this study. The descriptive-contrastive analysis of English and Ibaloy simple primary conjunctions presents the types of relationships of simple primary conjunctions with other word groups and subject predicate word groups.